Validity of the American Sign Language Discrimination Test. (October 2016) - Bochner, Joseph H.; Samar, Vincent J.; Hauser, Peter C.; Garrison, Wayne M.; Searls, J. Matt; Sanders, Cynthia A.
American Sign Language (ASL) is one of the most commonly taught languages in North America. Yet, few assessment instruments for ASL proficiency have been developed, none of which have adequately demonstrated validity. We propose that the American Sign Language Discrimination Test (ASL-DT), a recently developed measure of learners' ability to discriminate phonological and morphophonological contrasts in ASL, provides an objective overall measure of ASL proficiency. In this study, the ASL-DT was administered to 194 participants at beginning, intermediate, and high levels of ASL proficiency, a subset of which ( N  = 57) also was administered the Sign Language Proficiency Interview (SLPI), a widely used subjective proficiency measure. Using Rasch analysis to model ASL-DT item difficulty and person ability, we tested the ability of the ASL-DT Rasch measure to detect participant proficiency group mean differences and compared its discriminant performance to the SLPI ratings for classifying individuals into their pre-assigned proficiency groups using resource operating characteristic statistics. The ASL-DT Rasch measure outperformed the SLPI ratings, indicating that the ASL-DT may provide a valid objective measure of overall ASL proficiency. As such, the ASL-DT Rasch measure may provide a useful complement to measures such as the SLPI in comprehensive sign language assessment programs.